Genome-Wide Discovery of Microsatellite Markers from Diploid Progenitor Species, Arachis duranensis and A. ipaensis, and Their Application in Cultivated Peanut (A. hypogaea) - Zhao, Chuanzhi; Qiu, Jingjing; Agarwal, Gaurav; Wang, Jiangshan; Ren, Xuezhen; Xia, Han; Guo, Baozhu; Ma, Changle; Wan, Shubo; Bertioli, David J.; Varshney, Rajeev K.; Pandey, Manish K.; et al. (Frontiers in Plant Science, 2017)
Despite several efforts in the last decade towards development of simple sequence repeat (SSR) markers in peanut, there is still a need for more markers for conducting different genetic and breeding studies. With the effort of the International Peanut Genome Initiative, the availability of reference genome for both the diploid progenitors of cultivated peanut allowed us to identify 135,529 and 199,957 SSRs from the A (Arachis duranensis) and B genomes (A. ipaensis), respectively. Genome sequence analysis showed uneven distribution of the SSR motifs across genomes with variation in parameters such as SSR type, repeat number, and SSR length. Using the flanking sequences of identified SSRs, primers were designed for 51,354 and 60,893 SSRs with densities of 49.13 and 44.98 SSRs per Mb in A. duranensis and A. ipaensis, respectively. In silico PCR analysis of these SSR markers showed high transferability between wild and cultivated Arachis species. Two physical maps were developed for the A genome and the B genome using these SSR markers, and two reported disease resistance quantitative trait loci (QTLs), qF2TSWV5 for Tomato spotted wilt virus (TSWV) and qF2LS6 for leaf spot (LS), were mapped in the 8.135 Mb region of chromosome A04 of A. duranensis. From this genomic region, 719 novel SSR markers were developed, which provide the possibility for fine mapping of these QTLs. In addition, this region also harbors 652 genes and 49 of these are defense related genes, including two NB-ARC genes, three LRR receptor-like genes and three WRKY transcription factors. These disease resistance related genes could contribute to resistance to viral (such as TSWV) and fungal (such as LS) diseases in peanut. In summary, this study not only provides a large number of molecular markers for potential use in peanut genetic map development and QTL mapping but also for map-based gene cloning and molecular breeding.